2022
DOI: 10.3762/bjoc.18.79
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of α-(perfluoroalkylsulfonyl)propiophenones: a new set of reagents for the light-mediated perfluoroalkylation of aromatics

Abstract: In response to the demand for late-stage perfluoroalkylation in synthetic chemistry, we report the synthesis of a series of bench-stable α-(perfluoroalkylsulfonyl)propiophenones. Their application as photocleavable reagents was tested with electron-rich aromatics under metal-free, redox- and pH-neutral conditions to enable late-stage perfluorooctylation, perfluorohexylation, and perfluorobutylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…These "dummy group" reagents allow for easy installation of peruoroalkyl (peruorooctyl, peruorohexyl, peruorobutyl and triuoromethyl) group and also alkyl radicals (such as isopropyl and n-hexyl) on electron-rich aromatics and various biologically relevant substrates. 39 However, while a diverse set of peruoroalkyl and alkyl radicals were successfully utilized in this approach, the scope of the substrate is limited to molecules with minimal absorptions overlap to that of the "dummy" group (<290 nm) to achieve high photoconversion yields. It is noteworthy that while the literature pertaining to peruoroalkylation reactions is vast, [40][41][42][43][44] methods for the metal-free C-H peruoroalkylation of aromatic molecules through the use of EDA complexes in the catalytic regime remain limited.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These "dummy group" reagents allow for easy installation of peruoroalkyl (peruorooctyl, peruorohexyl, peruorobutyl and triuoromethyl) group and also alkyl radicals (such as isopropyl and n-hexyl) on electron-rich aromatics and various biologically relevant substrates. 39 However, while a diverse set of peruoroalkyl and alkyl radicals were successfully utilized in this approach, the scope of the substrate is limited to molecules with minimal absorptions overlap to that of the "dummy" group (<290 nm) to achieve high photoconversion yields. It is noteworthy that while the literature pertaining to peruoroalkylation reactions is vast, [40][41][42][43][44] methods for the metal-free C-H peruoroalkylation of aromatic molecules through the use of EDA complexes in the catalytic regime remain limited.…”
Section: Resultsmentioning
confidence: 99%
“…Having placed the pieces together in our mechanistic puzzle, we proceeded to optimize the proposed conditions and study the scope, while using our previously reported UV-light promoted perfluoroalkylating methodology as a ref. 39 . In the original report, 2 equivalents of the propiophenone-based perfluoroalkylating reagent were used to functionalize electron-rich aromatics under irradiation of a 300 W xenon arc lamp with a long-pass filter of >295 nm, reaching almost quantitative NMR yields for the perfluorohexylation of 1,3,5-trimethoxybenzene.…”
Section: Optimization Of Conditions and Expansion Of Scope: Visible-l...mentioning
confidence: 99%
See 1 more Smart Citation